68‐2: Distinguished Student Paper: Quantum Dot Light Emitting Devices (QLEDs) for Photomedical Applications. Issue 1 (2nd June 2017) - Chen, Hao; He, Juan; Lanzafame, Raymond; Stadler, Istvan; El Hamidi, Hamid; Liu, Hui; Celli, Jonathan; Wu, Shin-Tson; Dong, Yajie
Abstract : We demonstrate using an ultra‐bright quantum dot light emitting device for photobiomodulation (PBM) and photodynamic therapy (PDT). In‐vitro study indicates this approach could increase cell metabolism in multiple cell lines by ~12.5%–27.9% over control systems for PBM and kill cancerous cell efficiently for PDT.